Dengue Virus Induces the Expression and Release of Endocan from Endothelial Cells by an NS1–TLR4-Dependent Mechanism - Carlos Alonso Domínguez-Alemán; Luis Alberto Sánchez-Vargas; Karina Guadalupe Hernández-Flores; Andrea Isabel Torres-Zugaide; Arturo Reyes-Sandoval; Leticia Cedillo-Barrón; Ricardo Remes-Ruiz; Héctor Vivanco-Cid (Microorganisms, 2021)
A common hallmark of dengue infections is the dysfunction of the vascular endothelium induced by different biological mechanisms. In this paper, we studied the role of recombinant NS1 proteins representing the four dengue serotypes, and their role in promoting the expression and release of endocan, which is a highly specific biomarker of endothelial cell activation. We evaluated mRNA expression and the levels of endocan protein in vitro following the stimulation of HUVEC and HMEC-1 cell lines with recombinant NS1 proteins. NS1 proteins increase endocan mRNA expression 48 h post-activation in both endothelial cell lines. Endocan mRNA expression levels were higher in HUVEC and HMEC-1 cells stimulated with NS1 proteins than in non-stimulated cells (p < 0.05). A two-fold to three-fold increase in endocan protein release was observed after the stimulation of HUVECs or HMEC-1 cells with NS1 proteins compared with that in non-stimulated cells (p < 0.05). The blockade of Toll-like receptor 4 (TLR-4) signaling on HMEC-1 cells with an antagonistic antibody prevented NS1-dependent endocan production. Dengue-infected patients showed elevated serum endocan levels (≥30 ng/mL) during early dengue infection. High endocan serum levels were associated with laboratory abnormalities, such as lymphopenia and thrombocytopenia, and are associated with the presence of NS1 in the serum.